IMPLIKASI ASAS KEBEBASAN BERKONTRAK DALAM PRAKTEK PENGGUNAAN FORMAT-FORMAT KONTRAK - M. Nuzul Wibawa (Jurnal ADIL, 2019)
One thing that is common in most of case files submitted to the court is theambiguously multi-interpretational contracts or the imbalanced positions of the partiesinvolved, which consequently results in dispute instead of sustainable harmony betweenthem. This research applies normative method which involves literature study andrelated provisions of law. From the above explanation, it can be concluded that anyaspects related to legal contracts could potentially lead to dispute when none of theinvolved parties has the willingness to anticipate it. In practice, moreover, physicalform of legal contract might spark particular conflicts. Government, in this regardthrough relevant agencies, should play an active role in formulating clear, definitivestandard—including the one which regulates technical aspects—of legal contracts tominimize potential conflicts or disputes in the future.